CONTRIBUIÇÕES DA ROBÓTICA EDUCACIONAL PARA A APRENDIZAGEM DE TRIGONOMETRIA NA 1ª SÉRIE DO ENSINO MÉDIO DE UMA ESCOLA PARTICULAR DE LINHARES-ES - Gomes, Roger da Trindade (2021)
Exploratory Research, carried out with 16 students from the First Grade of High School, from the Eurico de Aguiar Salles Activity Center (SESI) located in Linhares-ES. The study deals with a didactic sequence in the form of workshops, in which student